Kesediaan Membayar Wisatawan Untuk Pelestarian Wisata Santai Beach Di Desa Latuhalat Kota Ambon - Talakua, Eygner Gerald (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2024)
One of the important tourist destinations in Ambon is Santai Beach, which offers beautiful beaches and sea so that the local government has designated it as a tourist area unit for diving activities. Behind the superior tourism potential, the management of Santai Beach needs to be improved. The important thing that needs to be managed is the change in the 108.67 m coastline that occurred over 10 years due to abrasion, due to damage to coastal protection structures. This damage can be overcome by placing concrete cubes randomly around the coral edge. The amount of funds or costs incurred to repair coastal damage can be estimated by determining compensation for damage to the coastline at Santai Beach. Determining compensation for damage to natural resources and the environment is approached by consumer valuation. Tourists can contribute to helping preserve tourist areas by paying for services or products when visiting. This research aims to analyze the value of tourists' willingness to pay for the preservation of Santai Beach tourism. The research used a survey method on 55 tourist respondents. Direct interviews with questionnaires and observations produce primary data which is mainly analyzed using the contingent valuation method, namely a direct method of economic assessment through asking someone's willingness to pay. The research results show that tourists who are willing to pay for the preservation of Santai Beach tourism are 10 people/two weeks or 76 people/month. The value of tourists' willingness to pay is IDR 2,272.73/person/month or IDR 172,727/month.